DETERMINANT OF INFLATION OF 5 ASEAN COUNTRIES - Imaduddin, Fadli; Pawirosumarto, Suharno; Zainudin, Zalina (International Journal of Psychosocial Rehabilitation, 2020)
This study is about five ASEAN countries, which are Malaysia, Indonesia, Singapore, Vietnam, and Thailand. The last three decades have been a great year for East Asia and South-East Asia because they have been growing rapidly in the sense of economic growth. According to (Lim & McAleer, 2004). The three newly industrializing countries (Malaysia, Indonesia, and Thailand) of South-East Asia have a growth rate of higher than double the rate by which the rest of East Asia since 1960. Singapore, on the other hand, is part of the Four Asian Tigers which is a high performing Asian economy and according to (McCarty, 2001), since the mid-1980s due to the Doi Moi reform period, the status of Vietnam changed from an economy of highly centralized command to a mixed economy by applying 5 years plan of directive and indicative planning. Vietnam is in the phase of integration the global economy and most of the companies in the country are small and medium enterprises. A major cause of inflation is the one when a government of the country focuses on producing unlimited money without central bank’s supervision. When there is lot of money in the market then it leads to increase the inflation. Thus, It is important that country should ensure a certain level of money supply which is according to the availability of the goods and services in the local market of a country. The production of the money needs to be controlled by the central bank. Moreover, some imported inflation is also present. This study aims to focus on the decline in the exchange rate of inflation.